MySQLAdminPro / Wong Teng Foong - Wong, Teng Foong (2006)
All final year undergraduates are required to carry out the final year project (thesis) which is divided into two phases. The first phase includes more on initial research, planning and study on the particular subject of field chosen. The second phase of the thesis is more emphasized on coding and development of system Each undergraduate will be assigned to a lecturer who acts as a supervisor responsible in advising and guiding the progress of the overall project. The undergraduate gets to choose the supervisor by either accepting the supervisor's thesis question or proposing his own question to the chosen lecturer My responsibility is to develop a tool which helps to manipulate the MySQL database. This tool helps to solve the unfriendly command line interface of MySQL by presenting user interfaces on a browser where buttons and links are used to operate the database. Other than that, the tool also equipped with a compressed backup function where it can backup databases in a compressed text file script format.